Auxerre - Abbaye Saint-Germain - Statue de saint Adrien - Benjamin Smith (Wikimedia Commons, 2025)
Notice iconographique issue de Wikimedia Commons. Titre: Auxerre - Abbaye Saint-Germain - Statue de saint Adrien. Auxerre (Yonne, France) - Former Saint Germanus abbey, now a museum - Statue of saint Adrian, 16th century
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; Wikimedia Commons